2021
DOI: 10.7762/cnr.2021.10.3.230
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pyridoxine Hydrochloride Supplementation on Leptin, Adiponectin, Glycemic Indices, and Anthropometric Indices in Obese and Overweight Women

Abstract: Obesity has reached epidemic proportions globally. Among several methods for treating obesity, the use of dietary supplements is common recently. One supplement that can help in this regard might be vitamin B6 in high doses. The objective of this study was to evaluate the effect of pyridoxine hydrochloride supplementation on anthropometric indices, body composition, visceral adiposity index (VAI), and metabolic status in obese and overweight women. In this randomized controlled clinical trial, 44 obese and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This results from the fact that food restrictions may cause inadequate iron intake, and symptoms of iron deficiency, including anemia [ 41 ], which is a common problem in young women [ 42 ]. At the same time, excessive body mass is by some authors indicated to be associated with deficiency or decreased intake of iron [ 43 ], as well as magnesium [ 44 ] and vitamin B6 [ 45 ], while in the conducted study, in the low-calorie diets, the intake of all these nutrients was reduced. Taking this into account, it should be indicated that some of the nutritional value alterations for the assessed low-calorie diets were not justified.…”
Section: Discussionmentioning
confidence: 99%
“…This results from the fact that food restrictions may cause inadequate iron intake, and symptoms of iron deficiency, including anemia [ 41 ], which is a common problem in young women [ 42 ]. At the same time, excessive body mass is by some authors indicated to be associated with deficiency or decreased intake of iron [ 43 ], as well as magnesium [ 44 ] and vitamin B6 [ 45 ], while in the conducted study, in the low-calorie diets, the intake of all these nutrients was reduced. Taking this into account, it should be indicated that some of the nutritional value alterations for the assessed low-calorie diets were not justified.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, meta-analyses did not report a significant effect of vitamin D supplementation on body weight reduction; however, a decrease in the BMI of adults with excess weight undergoing weight loss treatments [76] and in some specific population groups-such as females and Asians [77]-was noted.…”
Section: Effects Of Micronutrient Supplementation On Body Weight Redu...mentioning
confidence: 96%
“…The meta-analyses showed that only Ca administered to people with obesity and overweight allowed for a modest but statistically significant decrease of body mass by MD of −0.7 kg [81], while RCTs documented such an effect for vitamin B6 (MD −1.4 kg [77]), vitamin A (MD −1.5 kg [73]), and Se (MD −0.8 kg [82]) supplemented to dieting women with excess weight, women of reproductive age with obesity, and women with polycystic ovary syndrome who were given probiotics, respectively.…”
Section: Effects Of Micronutrient Supplementation On Body Weight Redu...mentioning
confidence: 99%
See 2 more Smart Citations